2004
DOI: 10.1159/000077497
|View full text |Cite
|
Sign up to set email alerts
|

Complex chromosomal rearrangements induced in vivo by heavy ions

Abstract: It has been suggested that the ratio complex/simple exchanges can be used as a biomarker of exposure to high-LET radiation. We tested this hypothesis in vivo, by considering data from several studies that measured complex exchanges in peripheral blood from humans exposed to mixed fields of low- and high-LET radiation. In particular, we studied data from astronauts involved in long-term missions in low-Earth-orbit, and uterus cancer patients treated with accelerated carbon ions. Data from two studies of chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…The biological reason for this long-term survival of such heavily damaged PBLs is unclear. However, similar observations, at varying frequencies, have been reported elsewhere including in plutonium workers [87][88][89][90], thorotrast patients [85,91], veterans of nuclear testing [92], A-bomb survivors [93], astronauts and patients receiving carbon therapy [81]. Interestingly, Hande et al [79] found a significant correlation with estimated plutonium dose to the bone marrow (from ~500mGy) and yield of complex aberrations suggesting quantification could potentially be used for dose reconstruction.…”
Section: Complexity Per Se As An Indicator Of High-let Radiationsupporting
confidence: 65%
“…The biological reason for this long-term survival of such heavily damaged PBLs is unclear. However, similar observations, at varying frequencies, have been reported elsewhere including in plutonium workers [87][88][89][90], thorotrast patients [85,91], veterans of nuclear testing [92], A-bomb survivors [93], astronauts and patients receiving carbon therapy [81]. Interestingly, Hande et al [79] found a significant correlation with estimated plutonium dose to the bone marrow (from ~500mGy) and yield of complex aberrations suggesting quantification could potentially be used for dose reconstruction.…”
Section: Complexity Per Se As An Indicator Of High-let Radiationsupporting
confidence: 65%
“…Slides were stained with either Giemsa for dicentric analysis, or painted with whole-chromosome DNA probes for fluorescent in-situ hybridization (FISH). The increase in aberrations during long-term missions was consistent with the values calculated from physical dosimetry data (Durante et al, 2004). In the present project, chromosomal analysis will be performed by examining chromosomal structure and also by utilizing immunohistochemistry.…”
Section: Chromosomal Analysissupporting
confidence: 80%
“…Mutations induced by space radiation could lead to carcinogenesis. The types of chromosomal aberrations induced by space radiation were translocations and complex exchanges seen in the cytogenetic analysis of lymphocytes of astronauts (Durante et al, 2003(Durante et al, , 2004George et al, 2002). Large individual differences in the frequency of these types of chromosomal aberrations were observed among astronauts.…”
Section: Biological Effects Of Space Radiationmentioning
confidence: 99%